2007
DOI: 10.4310/cms.2007.v5.n2.a11
|View full text |Cite
|
Sign up to set email alerts
|

Physical and numerical viscosity for quantum hydrodynamics

Abstract: Abstract. Viscous stabilizations of the quantum hydrodynamic equations are studied. The quantum hydrodynamic model consists of the conservation laws for the particle density, momentum, and energy density, including quantum corrections from the Bohm potential. Two different stabilizations are analyzed. First, viscous terms are derived using a Fokker-Planck collision operator in the Wigner equation. The existence of solutions (with strictly positive particle density) to the isothermal, stationary, one-dimensiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
28
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 38 publications
0
28
0
Order By: Relevance
“…Boundary conditions satisfying the Shapiro-Lopatinskii criterion have been examined in [12]. Furthermore, in [32,35] Dirichlet-type conditions have been employed in the analyzed, but only for the (simpler) one-dimensional equations.…”
Section: Proof First We Multiply (32) By Hmentioning
confidence: 99%
See 4 more Smart Citations
“…Boundary conditions satisfying the Shapiro-Lopatinskii criterion have been examined in [12]. Furthermore, in [32,35] Dirichlet-type conditions have been employed in the analyzed, but only for the (simpler) one-dimensional equations.…”
Section: Proof First We Multiply (32) By Hmentioning
confidence: 99%
“…For instance, in the Brenner-Navier-Stokes model with constant viscosity, Feireisl and Vasseur [17] proved that the density is positive except on a set of Lebesgue measure zero. Furthermore, in [35] it is shown that the solution of the one-dimensional stationary viscous quantum Euler model admits strictly positive particle densities.…”
Section: Proof First We Multiply (32) By Hmentioning
confidence: 99%
See 3 more Smart Citations